Draft Five Year Plan 1978-83 Mineral Development Government of Madhya Pradesh - Planning Commission (Planning Commission, 1978)
The department is mostly engaged in exploring the minerals and the exploitation has been entrusted to the M.P.State Mining Corporation Ltd. The Corporation's authorised capital is Rs. 50.00 lakhs and subscribed capital is Rs. 21.98 lakhs. The Corporation is exploiting, SMS Grade Limestone,.......... and dolomite, Pyrophyllite, Diaspore and Minor Minerals.
Government of Madhya Pradesh, Planning, Economics and Statistics Department